Green Constitution: An Analysis of Environmental Benefits and Environmental Restoration through Reclamation and Post-Mining Activities: Green Constitution: Tinjauan Kemanfaatan dan Pemulihan Lingkungan Hidup Melalui Reklamasi dan Pascatambang - Ranjani, Gita; Hendi Setiawan (Lex Renaissance, 2024)
The concept of the Green Constitution is embodied in the 1945 Constitution of the Republic of Indonesia through the recognition of the right to a good and healthy environment for the Indonesian people. This concept encourages the birth of laws related to environmental protection and management. In relation to sustainable development in the economic dimension, the mining sector is one of the largest drivers of Indonesia's economy and national development. However, mining activities generally cause environmental damage. Therefore, environmental restoration efforts are needed through the reclamation of ex-mining sites. This study aims to determine the concept of the Green Constitution reviewed from a utilitarian perspective and the concept of the Green Constitution in mining regulations in the context of environmental management and restoration through reclamation and post-mining. To sharpen the analysis, the research method used is juridical-normative with qualitative analysis and a legislative approach. The results of the study show, first, the concept of the Green Constitution according to the utilitarian view emphasizes that the state must create regulations that improve the welfare of its people, in terms of the environment and agrarian resources must prioritize the welfare of future generations through environmental management and restoration. Second, the concept of the Green Constitution in reclamation and post-mining at the normative level is found in the principles of good mining rules, principles of mining environmental protection, and reclamation and post-mining guarantee funds, but empirically it is still constrained by the lack of regulations at the level of Government Regulations which are derivatives of Law No. 3 of 2020 on Minerals and Coal.Keywords: green constitution, environment, post-mining, mining, utilitarian. AbstrakKonsep Green Constitution terejawantahkan dalam UUD NRI 1945 melalui pengakuan hak atas lingkungan hidup yang baik dan sehat bagi rakyat Indonesia. Konsep ini mendorong lahirnya undang-undang terkait perlindungan dan pengelolaan lingkungan hidup. Kaitannya dengan pembangunan berkelanjutan dalam dimensi ekonomi, sektor pertambangan menjadi salah satu penggerak perekonomian dan pembangunan negara terbesar di Indonesia. Namun, kegiatan pertambangan umumnya menyebabkan kerusakan lingkungan. Oleh karena itu, diperlukan upaya pemulihan lingkungan melalui proses reklamasi lahan bekas galian tambang. Penelitian ini bertujuan untuk mengetahui konsep Green Constitution ditinjau dari perspektif utilitarian serta konsep Green Constitution dalam peraturan pertambangan dalam konteks pengelolaan dan pemulihan lingkungan hidup melalui reklamasi dan pascatambang. Untuk mempertajam analisis maka metode penelitian yang digunakan adalah yuridis-normatif dengan analisis kualitatif dan pendekatan perundang-undangan. Hasil penelitian menunjukkan, pertama, konsep Green Constitution menurut pandangan utilitarian menegaskan bahwa negara harus menciptakan peraturan yang menyejahterakan rakyatnya, dalam hal lingkungan dan sumber daya agraria harus mementingkan kesejahteraan generasi mendatang melalui pengelolaan dan pemulihan lingkungan hidup. Kedua, konsep Green Constitution dalam reklamasi dan pascatambang pada tataran normatif ditemukan dalam prinsip kaidah pertambangan yang baik, prinsip perlindungan lingkungan pertambangan, serta dana jaminan reklamasi dan pascatambang, namun secara empirik masih terkendala oleh kekosongan regulasi pada tataran Peraturan Pemerintah yang merupakan turunan dari UU No 3 Tahun 2020 tentang Mineral dan Batubara.Kata kunci: green constitution, lingkungan hidup, pascatambang, pertambangan, utilitarian.